Housing affordability and pathways among Malaysian young professionals in greater Kuala Lumpur - Sohaimi, Nor Suzylah; Abdullah, Alias; Shuid, Syafiee (2017)
Young generation’s housing affordability study has recently increased as they have become the victims of the devastating consequences of house price volatility. This issue has been contentious among this cohort over the past three years due to stagnation of income in tandem with the increasing house prices. The research to date tend to involve the general young cohort rather than specific young groups such as the young professional, considering this cohort has distinctive characteristics associated to housing affordability. Thus, the purpose of this study is to identify the specific group of young professional and then to review housing affordability factors that underpin the residual income model and housing pathways concepts. Finally, a conceptual model of the study is proposed.